Quantitative modeling of bioconcentration factors of carbonyl herbicides using multivariate image analysis - Freitas, Mirlaine R.; Barigye, Stephen J.; Dare, Joyce K.; Freitas, Matheus P. (Chemosphere, 2016)
The bioconcentration factor (BCF) is an important parameter used to estimate the propensity of chemicals to accumulate in aquatic organisms from the ambient environment. While simple regressions for estimating the BCF of chemical compounds from water solubility or the n-octanol/water partition coefficient have been proposed in the literature, these models do not always yield good correlations and more descriptive variables are required for better modeling of BCF data for a given series of organic pollutants, such as some herbicides. Thus, the logBCF values for a set of carbonyl herbicides comprising amide, urea, carbamate and thiocarbamate groups were quantitatively modeled using multivariate image analysis (MIA) descriptors, derived from colored image representations for chemical structures. The logBCF model was calibrated and vigorously validated (r2 = 0.79, q2 = 0.70 and rtest2 = 0.81), providing a comprehensive three-parameter linear equation after variable selection (logBCF = 5.682 − 0.00233 × X9774 − 0.00070 × X813 − 0.00273 × X5144); the variables represent pixel coordinates in the multivariate image. Finally, chemical interpretation of the obtained models in terms of the structural characteristics responsible for the enhanced or reduced logBCF values was performed, providing key leads in the prospective development of more eco-friendly synthetic herbicides.
Keywords: Bioconcentration; Carbonyl herbicides; QSPR; Image analysis